2014
DOI: 10.1002/mnfr.201400124
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbial metabolism of olive oil phenolic compounds: In vitro and in vivo approaches

Abstract: The products of colonic catabolism of olive oil phenolic compounds could be good candidates for novel preventive strategies and open a promising line of research into the preventive action of olive oil phenols in colon and other bowel diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 45 publications
5
82
1
Order By: Relevance
“…In olive, the majority of polyphenols present belong to the tyrosol group [hydroxytyrosol (HT), tyrosol (TYR) and conjugated forms like oleuropein]. These conjugated forms are extensively hydrolyzed in the stomach [19] to HT and TRY, which are either absorbed in the small intestine and undergo extensive phase I and II biotransformation or reach the colon where they undergo biotransformation by the resident microbiota [19, 20]. The most common derivatives are small phenolic acids like homovanillic acid (HVA), dihydroxyphenylacetic acids (DHPAA), hydroxyphenylacetic acid (HPAA), protocatechuic acid and benzoic acids for example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In olive, the majority of polyphenols present belong to the tyrosol group [hydroxytyrosol (HT), tyrosol (TYR) and conjugated forms like oleuropein]. These conjugated forms are extensively hydrolyzed in the stomach [19] to HT and TRY, which are either absorbed in the small intestine and undergo extensive phase I and II biotransformation or reach the colon where they undergo biotransformation by the resident microbiota [19, 20]. The most common derivatives are small phenolic acids like homovanillic acid (HVA), dihydroxyphenylacetic acids (DHPAA), hydroxyphenylacetic acid (HPAA), protocatechuic acid and benzoic acids for example.…”
Section: Introductionmentioning
confidence: 99%
“…However, no data are reported for differences in metabolism of these compounds between men and women or indeed, whether such differences if they do exist, could be due to sex-specific differences in gut microbiota. To date, no studies have reported whether olives or olive pomace can impact on the relative abundances of the human gut microbiota, on the diversity of the gut microbiota and only a few studies have specifically addressed the metabolic end products produced by combined host–microbiota co-metabolism of olive polyphenols [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…EVOO’s phenolic compounds are rapidly hydrolyzed against alkaline conditions in the stomach and intestine, resulting in the increase of free HT to be absorbed in the small intestine where it forms phase II metabolites [11]. The in vitro colon fermentation of HT showed production of phenolic acids (phenylacetic and phenylpropionic acids) and degradation of HT-acetate and oleuropein by fecal culture medium, thus stabilizing HT and tirosol levels [28]. Furthermore, a moderate intake of a phenol-rich olive oil in males significantly raised the concentration in human feces of free HT [28].…”
Section: General Characteristics Of Hydroxytyrosolmentioning
confidence: 99%
“…The in vitro colon fermentation of HT showed production of phenolic acids (phenylacetic and phenylpropionic acids) and degradation of HT-acetate and oleuropein by fecal culture medium, thus stabilizing HT and tirosol levels [28]. Furthermore, a moderate intake of a phenol-rich olive oil in males significantly raised the concentration in human feces of free HT [28]. These data suggest a role for colon microbiota in HT biotransformation, leading to an enhanced biodisponibility of the polyphenol [28], and that the cardioprotective effects of EVOO observed in hypercholesterolemic subjects could be contributed by the increased populations of bifidobacteria and in phenolic microbial metabolites with antioxidant properties [29].…”
Section: General Characteristics Of Hydroxytyrosolmentioning
confidence: 99%
See 1 more Smart Citation